Mitochondrial p38β and Manganese Superoxide Dismutase Interaction Mediated by Estrogen in Cardiomyocytes - Liu, Han (Public Library of Science, 2014)
AIMS: While etiology behind the observed acceleration of ischemic heart disease in postmenopausal women is poorly understood, collective scientific data suggest cardioprotective effects of the endogenous female sex hormone, estrogen. We have previously shown that 17β-estradiol (E2) protects cardiomyocytes exposed to hypoxia-reoxygenation (H/R) by inhibiting p38α - p53 signaling in apoptosis and activating pro-survival p38β mitogen activated protein kinase (p38β MAPK), leading to suppression of reactive oxygen species (ROS) post H/R. However, little is known about the mechanism behind the antioxidant actions of E2-dependent p38β. The aim of this study is to determine whether the cytoprotection by estrogen involves regulation of manganese superoxide dismutase (MnSOD), a major mitochondrial ROS scavenging enzyme, via cardiac p38β. METHODS AND RESULTS: We identified mitochondrial p38β by immunocytochemistry and by immunoblotting in mitochondria isolated from neonatal cardiomyocytes of Sprague-Dawley rats. E2 facilitated the mitochondrial localization of the active form of the kinase, phosphorylated p38β (p-p38β). E2 also reduced the H/R-induced mitochondrial membrane potential decline, augmented the MnSOD activity and suppressed anion superoxide generation, while the dismutase protein expression remained unaltered. Co-immunoprecipitation studies showed physical association between MnSOD and p38β. p38β phosphorylated MnSOD in an E2-dependent manner in in-vitro kinase assays. CONCLUSION: This work demonstrates for the first time a mitochondrial pool of active p38β and E2-mediated phosphorylation of MnSOD by the kinase. The results shed light on the mechanism behind the cytoprotective actions of E2 in cardiomyocytes under oxidative stress.